2009
DOI: 10.3174/ajnr.a1698
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Anisotropy–Threshold Dependence in Tract-Based Diffusion Tensor Analysis: Evaluation of the Uncinate Fasciculus in Alzheimer Disease

Abstract: BACKGROUND AND PURPOSE:Tract-based analysis can be used to investigate required tracts extracted from other fiber tracts. However, the fractional anisotropy (FA) threshold influences tractography analysis. The current study evaluated the influence of the FA threshold in measuring diffusion tensor parameters for tract-based analysis of the uncinate fasciculus in subjects with Alzheimer disease (AD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 10 publications
2
35
0
1
Order By: Relevance
“…This makes the measurements slightly more objective and somewhat more speciˆc than ROI analysis, but one must keep in mind that the results diŠer depending on the arbitrarily chosen stop criteria. 48 This issue will be addressed again later.…”
Section: Ischemic Strokementioning
confidence: 98%
See 1 more Smart Citation
“…This makes the measurements slightly more objective and somewhat more speciˆc than ROI analysis, but one must keep in mind that the results diŠer depending on the arbitrarily chosen stop criteria. 48 This issue will be addressed again later.…”
Section: Ischemic Strokementioning
confidence: 98%
“…A recent study by Taoka's group has shown that the selection of the FA threshold in‰uences the measurement of diŠusion tensor parameters when tract-based analysis is performed. 48 It becomes apparent from this study that the operator-deˆned threshold of FA acts as aˆlter, below which all voxels are omitted from theˆnal analysis. Whether such arbitrary selection of threshold is clinically relevant remains unknown and warrants future research.…”
Section: Future Researchmentioning
confidence: 99%
“…Using the full tensor data, fractional anisotropy (FA) can be calculated for the index of the white matter anisotropic properties. These 2 metrics, ADC and FA, are now widely used to diagnose or evaluate disorders of the central nervous system, including stroke, 3 multiple sclerosis, 4 neoplasms, [5][6][7] neuropsychiatric disease, [8][9][10] and degenerative disease [11][12][13][14] in clinical situations. Despite their usefulness, however, FA and ADC have limitations.…”
Section: Introductionmentioning
confidence: 99%
“…FA constraints are routinely used for rough segmentation of WM and non-WM [27,41,42] making use of low anisotropy of GM and fluid. In particular, FA thresholds are used to constrain streamlines to WM regions in deterministic fibre tractography [43][44][45]. However, more accurate tissue segmentation as well as elimination of PVE in diffusion MRI images require an application of dedicated methods.…”
Section: Discussionmentioning
confidence: 99%